Pengaruh Leverage, Komisaris Independen, Kepemilikan Institusional Terhadap Agresivitas Pajak dengan Profitabilitas sebagai Variabel Intervening - Hana Zakiyah (Jurnal Riset Akuntansi Politala, 2026)
Abstract This study aims to analyze the impact of leverage, independent commissioners, and institutional ownership on tax aggressiveness by considering profitability as an intervening variable. This study was conducted on 12 companies in the transportation sector listed on the Indonesia Stock Exchange (IDX) during the 2019-2023 period. This study uses a quantitative approach with a multiple regression analysis approach to examine the relationship between these variables and the Sobel test on the intervening variable. The results of data processing yielded findings that leverage, independent commissioners, and institutional ownership negatively impact profitability. Meanwhile, leverage, independent commissioners, and institutional ownership negatively impact tax aggressiveness. The results of the R2 study indicate that the variables of leverage, independent commissioners, institutional ownership, and profitability simultaneously influence tax aggressiveness by 47.4%. Meanwhile, the results of the Sobel profitability test did not prove to be a mediator of the relationship between leverage, independent commissioners and institutional ownership